Potential of Analog Rice for Diabetes and Dyslipidemia: A Narrative Review of In Vivo Insight - Ariny Poespitasari; Fitriyono Ayustaningwarno; Ninik Rustanti (Journal of Health and Nutrition Research, 2026)
Analog rice is a potential alternative staple food for managing degenerative diseases, particularly type 2 diabetes mellitus (T2DM) and dyslipidemia. It can be formulated from various raw materials, including tubers, cereals, legumes, pulses, vegetables, and fruits, resulting in a product that resembles white rice. It contains bioactive compounds at levels comparable to or higher than that of white rice. The bioactive compounds, such as dietary fiber and resistant starch, function to slow glucose absorption and promote beneficial SCFA production, while the phenolic compounds act as potent antioxidants that may protect tissues from oxidative damage induced by hyperglycemia and dyslipidemia. This narrative review utilized PubMed, Scopus, ScienceDirect, and Google Scholar with keywords including "Analog rice","Diabetes Mellitus","Hyperglycemia","Dyslipidemia,", "Lipid profiles","Histopathology". The inclusion criteria comprised original English and Indonesian articles (2016-2026) evaluating in vivo analog rice interventions, selected through title, abstract, and full-text screening. The exclusion criteria were in vitro studies, human clinical trials, review articles, and non-peer-reviewed publications, resulting in 11 articles. The synthesized evidence suggests that analog rice consumption has potential benefits for reducing blood glucose levels, insulin levels, and the insulin resistance index (HOMA-IR), as well as improving pancreatic β-cell function (HOMA-β), increasing short-chain fatty acid (SCFA) production, and enhancing serum lipid profiles while reducing the atherogenic index (AI). Additionally, histopathological analysis showed tissue structure improvements, including in the β cells of the Langerhans islets, myocardial cells, and kidney cells. These findings suggest that analog rice has the potential to be effective in managing T2DM and dyslipidemia.